Legal liability for climate change impacts: strengthening the scientific basis - Stuart-Smith, RF (2022)
The courts have become an increasingly important venue for efforts to combat the impacts of climate change. Claims have brought on a range of legal grounds, but many climate lawsuits are based on the existence of a causal relationship between emissions of greenhouse gases and impacts that occur as a result. Such claims may be made to establish emitters’ liability for climate change impacts, or to demonstrate that contributions to climate change cause harm, and therefore that greenhouse gas emissions should be curbed.